Radical neo(realism) in the works of Cesare Zavattini - Borjan, Etami (2012)
The aim of the paper is to discuss the concept of (neo)realism in the works of the most prominent Italian neorealist screenwriter Cesare Zavattini. Zavattini combines several avant-garde tendencies that few years later will appear under the names of direct cinema or cinema verité in France: the use of photojournalist shooting methods, experimental realist cinema, abolition of the traditional narrative forms, tendency towards morally and politically engaged cinema, use of personaggi anagrafici - real people who re-enact the stories from the real life, the use of light equipment that allows closer relationship with the subjects, concept of cinema as a didactic tool, etc. The most important theoretician of neorealism stood for direct, spontaneous and immediate cinema as well as for the abolition of narrative fiction films. His contribution to the Italian film criticism of that period was enormous although his writings weren’t widely accepted because they were considered too radical.